THE ROLE OF MODERN EDUCATIONAL TECHNOLOGIES IN TEACHING MEDICAL STUDENTS - Larisa I. Knyazeva; Larisa A. Knyazeva; Igor I. Goryainov; Marina A. Stepchenko; Natalia S. Mescherina; Natalia A. Borisova (Высшее образование в России)
The article discusses of the role of modern educational technologies in pedagogical activity of the medical university department, perspectives of formation students' clinical thinking on the basis of competence-oriented approach. The authors analyze innovations accompanying the modern concept of modular education, and propose variants of modern technology usage as a part of education of future doctors. The authors present possibilities of context and problem education when teaching senior students. The article contains the information on the most advanced educational technologies imitating the future occupational activity of medical students and implemented at the department of internal diseases No. 1 of Kursk State Medical University. It is concluded that innovative educational technologies should be certainly used as they enable to organize an educational process so that it is possible to achieve the main purpose - formation of students' professional competences.